Designing for change: performative and flexible approaches to contemporary housing - Kassem, Ayman; Eldanaf, Taher Salah; Camponogara, Marcella; Hamdan, Wael (Frontiers in Built Environment, 2025)
Contemporary housing must accommodate demographic volatility, climatic extremes, and evolving household structures. This article develops an integrated framework for “designing for change” that aligns four lenses: flexibility (design method), adaptability (long-term functional capacity), performativity (environmental interaction), and calibrated incompleteness (resident agency) to reposition housing as an open system rather than a finished object. Drawing on Open Building and Open Form theory, we test the framework through comparative case studies that bridge global precedents (e.g., Elemental’s incremental housing; Doshi’s Aranya housing) and Gulf Cooperation Council (GCC) applications (e.g., BaityKool, Masdar Eco-Villa, Dubai’s policy reforms, and Saudi developments such as ROSHN Sedra and TAG Villa). Findings indicate that effective GCC housing couples lightweight, modular “hardware” with policy-enabled elasticity and passive-active environmental systems, enabling staged growth, post-occupancy modification, and culturally specific patterns of use. The article argues that flexibility is a sociotechnical and sociocultural imperative requiring regulatory foresight, material innovation, and meaningful participation. It concludes with an agenda for measurement (post-occupancy adaptability metrics), governance (codes that normalize change), and pedagogy (time-based design rehearsal), offering transferable lessons for resilient, inclusive, and climate-responsive housing.